Characterization of chitin preparations using powder and film X-ray diffraction methods. Issue 1 (March 2013) - Deschamps, Jeffrey R.
Abstract : Chitin is a natural polysaccharide found in many diverse phyla and almost always occurs in association with protein. In this study the chitin polymer is characterized by X-ray diffraction from its naturally occurring unprocessed state through various steps used in the purification procedure. In addition, the effect of different treatments on the final product is examined. These studies show that native chitin has a characteristic diffraction pattern that is not altered by the mild treatments used to isolate relatively pure chitin. Chitins prepared from different sources exhibit the same characteristic diffraction pattern. In addition, chitin films prepared using non-degrading solvents retain most of the characteristic patterns. De-acylation of chitin to produce chitosan results in large changes to the diffraction pattern. To a very limited extent features present in the diffraction pattern of native chitin can be recovered by re-acylation of chitosan.